2002
DOI: 10.5483/bmbrep.2002.35.6.604
|View full text |Cite
|
Sign up to set email alerts
|

RU486 Suppresses Progesterone-induced Acrosome Reaction in Boar Spermatozoa

Abstract: The effects of progesterone on the acrosome reaction, as well as the effects of RU486 on the progesterone-induced acrosome reaction in capacitated boar spermatozoa, were investigated. Progesterone, a major steroid that is secreted by the cumulus cells of oocyte, clearly induced the acrosome reaction in a dose-dependent manner in capacitated boar spermatozoa, even though it failed to show similar effects in non-capacitated spermatozoa. RU486, a potent antiprogestin, significantly reduced the effects of progeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…Lately, non-genomic mPRs have been reported in conjunction with non-genomic functions of progesterone (Zhu et al 2003). In mammalian reproduction, progesterone has been implicated to be involved in AR (reviewed by Calogero et al 2000), in human (Osman et al 1989, Baldi et al 1995, Patrat et al 2000, mouse (Melendrez et al 1994), stallion (Meyers et al 1995), golden hamster (Meizel et al 1990), dog (Sirivaidyapong et al 1999), goat (Somanath et al 2000 and boar (Jang & Yi 2002). Progesterone, by binding to a non-genomic mPR, has been reported to induce AR via intracellular signal transduction cascades (Kopf 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, non-genomic mPRs have been reported in conjunction with non-genomic functions of progesterone (Zhu et al 2003). In mammalian reproduction, progesterone has been implicated to be involved in AR (reviewed by Calogero et al 2000), in human (Osman et al 1989, Baldi et al 1995, Patrat et al 2000, mouse (Melendrez et al 1994), stallion (Meyers et al 1995), golden hamster (Meizel et al 1990), dog (Sirivaidyapong et al 1999), goat (Somanath et al 2000 and boar (Jang & Yi 2002). Progesterone, by binding to a non-genomic mPR, has been reported to induce AR via intracellular signal transduction cascades (Kopf 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The AR can be induced by follicular fluid, cumulus cells (Tesarik et al 1993) or the ZP (Cross et al 1988). Identified as the active component of follicular fluid, progesterone, a steroid hormone known to induce transcriptional activations in the nucleus mediated by an intracellular receptor, has been reported to induce the AR in many mammalian spermatozoa (Osman et al 1989, Meizel et al 1990, Melendrez et al 1994, Baldi et al 1995, Meyers et al 1995, Sirivaidyapong et al 1999, Patrat et al 2000, Somanath et al 2000, Jang & Yi 2002, which strongly implies that progesterone exerts its effect on mammalian spermatozoa non-genomically via a still unidentified membrane-bound progesterone receptor (mPR). Although the mechanism is poorly understood, the AR induced by progesterone is regulated by signal transduction processes upon progesterone binding onto a still unidentified mPR.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the effect of the tannins on AR induction of capacitated sperm, a portion of the preincubated sperm was treated with 10 µg/ml progesterone in the presence or absence of 5 µg/ml of the tannins for 30 min at 39 C in an atmosphere of 5% CO 2 in air to induce AR as described previously [25]. Other preincubated sperm were coincubated with cumulus-free oocytes or extensively pretreated oocytes with 500 units/ml h y a l u r o n i d a s e f o r 2 h i n I V F m e d i u m supplemented with or without 5 µg/ml of the tannins for 2 h, and then sperm-oocyte complexes were gently rinsed several times with PBS using a wide-bore pipette to remove loosely attached spermatozoa.…”
Section: Evaluation Of Sperm Acrosome Statusmentioning
confidence: 99%
“…As prematurely acrosome reacted sperm cannot undertake fertilisation [42] and progesterone, at micromolar concentrations, has previously been reported to cause the acrosome reaction in capacitated boar sperm [21,22] we sought to assess if the enhanced swim rate would be compromised by a parallel increase in the acrosome reaction. We demonstrated that the acrosome reaction is increased in the population of capacitated cells treated with 100nM progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the effects of progesterone on boar sperm cells have largely focussed on its effects on the acrosome reaction [21][22][23]. However, high (micromolar) concentrations have been reported to increase motility [24] and intracellular calcium levels [14] in capacitated cells.…”
Section: Introductionmentioning
confidence: 99%